Introduction to the Special Issue on Cultural Adaptations of CBT. (24th October 2018) - Stone, Lydia; Beck, Andrew; Hashempour, Faramarz; Thwaites, Richard
Abstract : Cognitive behaviour therapy (CBT) has become the first line of treatment for a wide range of mental health problems across many countries. The flexibility of CBT, and a strong evidence base and good track record of training and dissemination, has lent itself to scaling up of this therapy, and projects such as the Improving Access to Psychological Therapies (IAPT) programme in England have shown that large-scale projects to roll out CBT at a national level are possible (Clark, 2011 ).